Virtual Cycling For Promoting a Healthy Lifestyle - Catur Supriyanto; Bing Liu (International Journal of Science, Technology & Management, 2021)
The pandemic era has brought a rapid change in the human health lifestyle. Considering the importance of a healthy lifestyle, many companies have started to promote indoor exercises to encourage a healthy lifestyle. Recently, virtual cycling is one of the popular virtual sports in Asia, European Countries, and the USA. This paper presents the evaluation of virtual cycling for promoting a healthy lifestyle. This paper aims to share a virtual cycling exercise's strengths and challenges based on empirical studies. Document analysis was done on the existing empirical studies from the online journal and news papers articles. The finding suggests that virtual cycling is healthy, fun, and a low-impact virtual form of virtual exercise that becomes a lifestyle. Some recommendation was suggested for the development of virtual cycling for the sustainable health community.